Victoria of many faces. 1 - Syuu (Yen Press, 2025)
"When news of Chloe's death reached her handler, he couldn't believe it. His premier operative dashed against the rocks, never to be seen again--just how Chloe planned it! After the organization betrayed her, she hatched a daring escape plan and landed in the kingdom of Ashbury under a new name--Victoria! Stopping a thief, adopting a lost child, and capturing the heart of the nation's dreamiest knight on her first day in town is nothing to a former superspy. She'll have to keep her head down to avoid the prying eyes of her new compatriots and old employer. But hey, don't retired spies deserve a chance at love, too?"--